Pesan Dakwah dalam Buku The Miracle of Giving - Ahmad Harun Yahya; Habibun Nazar; Manalullaili Manalullaili (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2019)
Da’wah needs to be packed with various means, not only by the way of face to face so that da’wah is not limited by space and time. Da’wah can be done through written or oflen also called da’wah bil qalam which is means and method of conveying da’wah messages to mad’u through print media, one of these are the work of books. Accordance with this, the islamic books that contrained the message of preaching was born the book “The Miracle of Giving by Yusuf Mansur. The research method which used is a qualitative method with a conten analysis approach, which is a research technique to obtain an overview the contents of the da’wah message that contained in the book. The contents of the message of da’wah that contained in strategy which used by Yusuf Mansur in preaching is invite people to love charity throgh the strategy and storyfeling strategy based on true stories.